Seasonal Dynamics and Role of Substrate Quality in Leaf Litter Decomposition of Different Agro forestry Tree Species - Kaushal, R.; Verma, K.S.; Singh, K.N. (Indian Journal of Agroforestry, 2020)
Decomposition patterns of Grewia optiva,Morus alba, Toona ciliata and Populus deltoides tree leaves were studied by placing the leaf litter in surface and plough/sub-surface layer. Decomposition rate was highest in Mops followed by Grewia, Toona and Populus for both the placements. Sub-surface placed litter showed faster rate of decomposition than surface placed leaf litter. Rate of decomposition in all the four species was influenced significantly and positively due to rainfall and temperature except Populus, where temperature had no influence on decomposition rate. Relationship between cumulative weight loss and substrate/litter quality attributes viz., Ca, acid detergent fiber (ADF), lignin and cellulose was significant but negative. The correlation coefficient values further depicted an increase with lapse of time i.e. from winter through summer to rainy season thus showing its importance during the later stages of decomposition. Nitrogen and water-soluble compounds (WSC) content on the other hand showed positive and significant correlation with cumulative weight loss.